Statistics and informatics in molecular cancer research - Wiuf, Carsten; Andersen, Claus L. (Oxford : Oxford University Press, 2009)
Molecular understanding of cancer and cancer progression is at the forefront of many research programs. Complex mathematical, statistical and bioinformatics tools are required to extract, handle and process data and this book aims to make these tools available to a wide range of researchers, in a single coherent volume.
Description based on print version record.
Keywords: Cancer -- Research -- Statistical methods; Cancer -- Research -- Data processing; Cancer -- Molecular aspects -- Research -- Data processing; Cancer -- Molecular aspects -- Research -- Statistical methods